Mosquitoes and their perceived nuisance in Tripoli - Aqeehal, Hanan; Saadawi, Walid; Qashsh, Hanaa; Alshibani, Manal; Elgrari, Ahmed (International Journal of Scientific Research in Biological Sciences, 2021)
Despite the high numbers of mosquitoes observed in some areas, little is known about the biting nuisance of mosquitoes in Libya. Tripoli municipality is a place notorious for nuisance mosquitoes perceived in year 2015, The objective was to assess the impact of mosquito nuisance on the residents of Tripoli municipality and to show results of mosquitoes collected during the nuisance outbreak. Two hundred people were randomly selected and asked if they had been bitten by mosquitos. If they said yes, they were asked to explain where and when they were attacked by mosquitos, as well as what precautions they took to avoid mosquito bites. The questionnaire was filled out by 160 participates. 65% of those reported being bitten by mosquitoes, with most bites occurring outdoors during the summer. Thirty-nine percent said most of the biting happened in the evenings and at night. 43 (27%) took protective measures against being bitten. Of those respondents who protected themselves against biting using repellents (44%), with the remainder changing their behavior to avoid mosquitoes, including closing or screening windows and windows or doors screen with (35%), (2%) respectively, wearing thicker clothes (4%) and spraying insecticide (21%).one person stayed inside (2.3%). Mosquitoes are a major issue for a large section of Tripoli`s population, according to this study. Given the growing worry about the threat posed by potential and emerging viruses in Libya, health officials need to make major efforts to alert the public about the threats posed by mosquitoes in areas where they are common.